JADE Multi-agent Middleware Applied to Contribute to Certificate Management of Students - Fatiha Aityacine; Badr Hssina; Belaid Bouikhalene (Institute of Advanced Engineering and Science, 2015)
In this article, we present a multi-agent approach that aims to design, modeling and implementation of an application